ERP System for Construction Site - Muhammad Waheed; Mutahir Abbas (International Journal of Integrative Sciences, 2023)
Currently, enterprise resource planning (ERP) has been recognized as a foundation for the merging of organization-wide data systems. ERP systems connect all aspects of an organization's business, including accounting, finance, human resources, production, and distribution. They also connect the company to its consumers and suppliers across the many phases of the product's or process' life cycle. Just a few studies have been done on the use of ERP systems on construction sites, particularly for designers, technicians, and workers. the main focus has thus far been on retail businesses, engineering companies, and design firms. The purpose of this study is to conduct research on the effectiveness of ERP systems at contractor sites and, as a result, their implementation status. A wide range of market research, literature reviews, and modified surveys may be used as the methodology. The majority of contractor sites are reported to be aware of ERP systems, although only a small number of organizations have so far implemented such systems. The main reason is that every ERP system adoption requires a significant time, financial, and resource investment. However, if used to solve the right issues, these ERP systems could be a successful tool for business development